Predation Cues Lead to Reduced Foraging of Invasive Siganus rivulatus in the Mediterranean - Shapiro Goldberg, Daphna; Rilov, Gil; Villéger, Sébastien; Belmaker, Jonathan (Frontiers in Marine Science, 2021)
Invasive species are one of many anthropogenic challenges to maintaining a healthy marine ecosystem. Two rabbitfish species (Siganus rivulatus and Siganus luridus) are among the more successful migrants from the Red Sea to the Mediterranean, where their intense foraging has caused damage to the algae community, thus reducing primary production and habitat complexity, and impacting nurseries for early life stages. Anecdotal evidence suggests that the impact of rabbitfish on algae is lower in Marine Protected Areas (MPAs) although rabbitfish densities are similar in protected and fished areas. One explanation could be that fear of predators, more often present inside MPAs and an important component of a healthy marine ecosystem, reduces the ecological impacts of rabbitfish. This research aimed to test if such fear effects do occur in rabbitfish. Using controlled mesocosm experiments, we tested S. rivulatus reactions to two chemical predation cues: chemical alarm cues released from a recently killed conspecific fish, and water-borne cues from a tank with a live grouper predator, Epinephelus marginatus. We found that rabbitfish significantly reduce their overall food consumption as well as their bites per minute when exposed to the alarm cue, but not when exposed to the grouper water cue. These results support the idea that MPAs, which effectively increase the density of large piscivores and hence predation, can mitigate the impact of invasive herbivorous species. If the mesocosm results can scale up to natural systems, predation cues may be artificially introduced to other target areas in order to reduce rabbitfish grazing outside reserves. Thus, this study provides information that can be used to manage the ecological impacts caused by invasive rabbitfish, both inside and outside of marine reserves.